1978
DOI: 10.1111/j.1432-1033.1978.tb12030.x
|View full text |Cite
|
Sign up to set email alerts
|

Blue‐Dextran — Sepharose Affinity Chromatography: Recognition of a Polynucleotide Binding Site of a Protein

Abstract: Native Escherichia coli polynucleotide phosphorylase can be retained on blue-dextran -Sepharose. The bound enzyme cannot be displaced by its mononucleotide substrates such as ADP, UDP, CDP, G D P and IDP, but it is easily eluted by its polymeric substrates. Under identical conditions, lactate dehydrogenase, bound on blue-dextran -Sepharose, is not eluted by poly(1) but can be specifically displaced by NADH. On the other hand, the trypsinized polynucleotide phosphorylase, known to be an active enzyme which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Such chromatography not only allows the separation of proteins having a polynucleotide-binding site from other classes of proteins but also can be used to separate one native enzyme from a degraded enzyme that has lost the polynucleotide attachment site (7). The methodology was also applied to the characterization and purification of both viral and immune interferons (8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such chromatography not only allows the separation of proteins having a polynucleotide-binding site from other classes of proteins but also can be used to separate one native enzyme from a degraded enzyme that has lost the polynucleotide attachment site (7). The methodology was also applied to the characterization and purification of both viral and immune interferons (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…We have recently described an affinity chromatography with blue dextran or polynucleotide as ligand for proteins interacting with nucleic acids (7). Such chromatography not only allows the separation of proteins having a polynucleotide-binding site from other classes of proteins but also can be used to separate one native enzyme from a degraded enzyme that has lost the polynucleotide attachment site (7).…”
mentioning
confidence: 99%
“…Cibacron blue is a non-competitive inhibitor with respect to dinucleotide for dihydrofolate reductase, but competitive with dihydrofolate: this agrees with a binding in the substrate binding site [ 3 ] . Furthermore it has been suggested that the dye binds to the polynucleotide binding site in polynucleotide phosphorylase rather than in the mononucleotide binding site [8].…”
mentioning
confidence: 99%
“…Strong binding of blue dextran to NAD(P)+-dependent dehydrogenases seems to be frequent [3], but many other enzymes also interact with blue dextran or Cibacron: enzymes acting on NAD' like NAD' glycohydrolase [4], NAD' kinase [5] as well as nucleotide-dependent enzymes such as nucleotide kinase [6], nucleotidetransferase [6], adenylate cyclase [7], polynucleotide phosphorylase [8], phosphorylase a [9], hexokinase [lo] and flavocytochrome h~, a flavin-dependent enzyme [l 11. Conformational changes of Cibacron blue bound to dehydrogenases were detected by circular dichroism [12].…”
mentioning
confidence: 99%
“…CB, a sulfonated polyaromatic dye, has been shown to bind to several proteins that interact with nucleotide substrates, nucleotide coenzyme ligands, and polynucleotides (13)(14)(15)(16)(17)(18). In the case of enzymes that have polynucleotide binding sites in addition to nucleotide substrates, the dye interacts with the polynucleotide binding site preferentially (15,17,18). In associated with the cellulose pellet was measured in a Beckman scintillation counter (LS-250) using Bifluor scintillation fluid.…”
mentioning
confidence: 99%